Pseudofinder: Detection of Pseudogenes in Prokaryotic Genomes. (8th July 2022) - Syberg-Olsen, Mitchell J; Garber, Arkadiy I; Keeling, Patrick J; McCutcheon, John P; Husnik, Filip
Abstract: Prokaryotic genomes are usually densely packed with intact and functional genes. However, in certain contexts, such as after recent ecological shifts or extreme population bottlenecks, broken and nonfunctional gene fragments can quickly accumulate and form a substantial fraction of the genome. Identification of these broken genes, called pseudogenes, is a critical step for understanding the evolutionary forces acting upon, and the functional potential encoded within, prokaryotic genomes. Here, we present Pseudofinder, an open-source software dedicated to pseudogene identification and analysis in bacterial and archaeal genomes. We demonstrate that Pseudofinder's multi-pronged, reference-based approach can detect a wide variety of pseudogenes, including those that are highly degraded and typically missed by gene-calling pipelines, as well newly formed pseudogenes containing only one or a few inactivating mutations. Additionally, Pseudofinder can detect genes that lack inactivating substitutions but experiencing relaxed selection. Implementation of Pseudofinder in annotation pipelines will allow more precise estimations of the functional potential of sequenced microbes, while also generating new hypotheses related to the evolutionary dynamics of bacterial and archaeal genomes.